OPTIMIZING ISLAMIC RELIGIOUS EDUCATION LEARNING THROUGH SELF-REGULATED LEARNING FOR STUDENTS: A SYSTEMATIC LITERATURE REVIEW - M. Nuzulul Ulum; Mia Rosiana Mahmudah; Dedi Hendrianto; Ahmad Bayu Permana (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze and synthesize various studies regarding the optimization of Islamic Religious Education learning through the Self-Regulated Learning (SRL) approach for students. The study employed the Systematic Literature Review (SLR) method using the PRISMA guidelines, which include the stages of identification, screening, eligibility, and included. The data were obtained from scientific journal articles published between 2020 and 2025 through the Google Scholar database using the keywords Self-Regulated Learning, Islamic Education, and Islamic Religious Education Learning. The findings indicate that Self-Regulated Learning makes a significant contribution to improving students’ learning independence, strengthening learning motivation, and helping students manage the learning process more systematically through the stages of planning, monitoring, and evaluation. In addition, the integration of Islamic values such as patience, discipline, and responsibility, as well as the utilization of digital technology in learning, also play an important role in strengthening students’ self-regulation abilities. These findings demonstrate that the implementation of Self-Regulated Learning can serve as an effective strategy in optimizing the quality of Islamic Religious Education learning, which is oriented not only toward cognitive aspects but also toward the development of students’ character and spiritual awareness.